Integration and optimization of electrified LNG steam reforming hydrogen production system - Huchao SONG; Jinghao FENG; Shuman WANG; Yuhang XI; Xirui MA; Yinhe LIU (You-qi chuyun)
The global demand for clean hydrogen energy is constantly increasing. However, the methane steam reforming process cannot satisfy the future social demand for clean hydrogen energy due to its high emission, while the development of water electrolysis technology via renewable energy is limited due to the high cost and the low efficiency. In response to the above issues, an electrified LNG steam reforming hydrogen production system was proposed by introducing the renewable electric heating into the methane steam reforming process, which efficiently integrates the carbon capture technology and the LNG cold energy recovery system. Meanwhile, a model of the electrified LNG steam reforming hydrogen production system was established, and its thermodynamic performance was analyzed. On this basis, investigation was conducted on the influence of the reforming temperature, water-to-carbon ratio and other key parameters on the exergy efficiency and electrical efficiency of the system. The research shows that the exergy efficiency and electrical efficiency of the novel hydrogen production system are as high as 83.2% and 89.5% respectively, and the electrical efficiency is 12.3% higher than the mainstream water electrolysis hydrogen production system. Generally, the novel hydrogen production system could achieve an efficient and clean hydrogen energy supply, providing a new idea and solution to achieve hydrogen production by renewable electricity.